2009
DOI: 10.1055/s-0029-1242205
|View full text |Cite
|
Sign up to set email alerts
|

Tibial Intervention for Critical Limb Ischemia

Abstract: Diagnosis and treatment of critical limb ischemia (CLI) is increasingly important as the average age of the world population and the incidence of diabetes and metabolic syndrome increases. Fortunately, most patients will not progress to this stage of peripheral arterial disease, yet if left untreated, there is a high risk of future cardiovascular events. At the point of ischemic rest pain or tissue loss, there are significant implications for morbidity and mortality. There is a high prevalence of multisegment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
4
0
2
Order By: Relevance
“…[97][98][99][100] The proposed mechanism of these techniques is to increase target lesion compliance, thereby reducing the risk of flow-limiting dissection and improving the immediate results of BA. 101 Cutting and scoring balloons may improve the outcomes of angioplasty compared with standard BA. 102 Cardon et al 102 investigated 48 elderly patients with CLTI and reported an 81% 1-year limb salvage rate.…”
Section: Residual Stenosismentioning
confidence: 99%
See 1 more Smart Citation
“…[97][98][99][100] The proposed mechanism of these techniques is to increase target lesion compliance, thereby reducing the risk of flow-limiting dissection and improving the immediate results of BA. 101 Cutting and scoring balloons may improve the outcomes of angioplasty compared with standard BA. 102 Cardon et al 102 investigated 48 elderly patients with CLTI and reported an 81% 1-year limb salvage rate.…”
Section: Residual Stenosismentioning
confidence: 99%
“…97–100 The proposed mechanism of these techniques is to increase target lesion compliance, thereby reducing the risk of flow-limiting dissection and improving the immediate results of BA. 101…”
Section: Failure Mechanisms After Infrapopliteal Bamentioning
confidence: 99%
“…Конвенциональные вмешательства остаются вынужденной мерой оказания помощи, в том числе в тех случаях, когда гибридные технологии не позволяют надеяться на успех в связи с особенностями атеросклеротического процесса (протяженность поражения, выраженность кальциноза и др.) [8]. В выполненном исследовании наиболее значимые отклонения липидного обмена оказались связаны с большой частотой инфекционных и тромботических ослож нений в группе ОВ.…”
Section: Discussionunclassified
“…A 2009 review of the state of tibial interventions for critical limb ischemia (CLI) summarized the deficiencies of the current literature by pointing out a lack of data to determine "the most appropriate and beneficial role of endovascular intervention," as well as a marked need for comparative data pertaining to treatment methods. 8 Furthermore, the impact of patient factors (eg, comorbidities) on each treatment is yet to be elucidated and significantly affects both technical and patient-oriented outcomes. 9 Given the significantly increased cost and procedural time associated with the use of newer atherectomy techniques as compared with PTA, 10 data directly comparing the efficacy and outcomes of PTA vs atherectomy-assisted intervention when used to treat tibial occlusive disease is necessary in order to best determine the place for each technique in infrapopliteal interventions.…”
Section: Studies Of Percutaneous Infrainguinal Interventionsmentioning
confidence: 99%